An in vivo study on the therapeutic value of alum on induced traumatic ulcers in guinea pigs - Gochan, Ma. Merced; Medina Vicente III.; Estaniel Cynthia P. (Adviser).
This paper attempts to study the effect of alum treatment on the healing of traumatic ulcers. Ten guinea pigs were used in this experiment and all had induced traumatic ulcers placed on their lower lip mucosa with the use of the electrocautery unit. Five of these guinea pigs had their ulcers treated twice a day with alum while the rest did not receive any treatment for their traumatic ulcers. It was found the healing in the guinea pigs that had alum treatment occured 2-3 days earlier than the guinea pigs that did not received alum treatment. Histologically, the progress of healing in both groups did not differ much.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Alum (Tawas) -- Therapeutic use